ANALISIS PENERAPAN SISTEM INFORMASI PEMBELAJARAN BERBASIS CLOUD DALAM PENDIDIKAN - Kesya, Amanda Nikita; Alfin Fadillah; Muhamad Syaifulloh Ramadhan (CV SWA Anugerah, 2025)
The application of cloud-based learning information systems in education has become a significant innovation in supporting the teaching and learning process in the digital era. This research aims to analyze the effectiveness, efficiency and challenges in implementing cloud technology in learning systems. Using qualitative and quantitative approaches, data was obtained through literature studies, interviews with teaching staff, and surveys of students. The research results show that cloud-based systems increase the accessibility of learning materials, expand collaboration between students and teachers, and reduce dependence on physical infrastructure. However, there are challenges such as the need for a stable internet connection, platform subscription costs, and user data and privacy protection. This study recommends strategic steps to increase the adoption of cloud technology in education, such as developing data security policies and technology training for users. With proper implementation, cloud-based learning information systems have great potential to improve the overall quality of education.